Análisis del índice de selección del programa de mejoramiento genético sostenible de bovinos de leche de la parroquia Tanicuchi periodo 2023. - De la Cruz Naranjo, Lida Narcisa (2024)
The objective of this research is to analyze the selection index of the sustainable genetic improvement program of the Tanicuchi parish. To evaluate the performance of the selected and weighted traits in the selection index, determining their impact on milk production and reproductive efficiency of the selected animals. With this information we were able to identify the individuals with the best scores in terms of genetic value (EBV) and response to selection (RS) of each trait taken into account for the study, thus obtaining the 10 best individuals that respond positively to the trait daily weight gain to EBV and RS are Mora 139.74 gr/day; 155.72 gr/day, Sultana 136.96gr/day;152.93 gr/day, Perinola 135.95gr/day; 151.93 gr/day, Pillareña 132.82gr/day; 148.80 gr/day, Macaria 85.72 gr/day; 101.69 gr/day, Diabla 79.35 gr/day; 95.33 gr/day, Maruja 68.19 gr/day; 84.17 g/day, Valentina 62.45 g/day; 78.43 g/day, Zapatitos Blancos 60.45 g/day; 76.42 g/day, Aleja 57.97 g/day; 73.95 g/day, this being the most important trait in the genetic improvement program for the Tanicuchi parish. Another objective was to identify the main strengths and weaknesses of the selection index used in the genetic improvement program, to meet this objective the calculation and statistical analysis of the data collected was performed, thus obtaining the response to the selection, from this result it is established that the character height at the withers (122, 45cm) is the main strength, as for the weaknesses, the character weight gain (12.89 gr/day), milk production (2972.1kg/lactation), and milk density (0.93 gr/ml) are the main weaknesses since the result obtained was lower than the ideal value of the characters taken into account. To fulfill the last objective, which is to perform a cost-benefit analysis of the genetic improvement program, data were collected from each cattle farm registered in the project to obtain a database that allows us to calculate the cost of production for a liter of milk for the Tanicuchi parish, thus obtaining an average production cost of $0.12 for a liter of milk